#### Solved Examples and Worksheet for Finding Missing Number using Multiplication or Division

Q1Which of the numbers will make the expression true?
3 × ___ = 9

A. 2
B. 1
C. 4
D. 3

Step: 1
Substitute the choices in the expression to check which number makes the expression true.
Step: 2
Substitute 2 in the expression, 3 × 2 = 6 and 6 < 9.
Step: 3
Substitute 1 in the expression, 3 × 1 = 3 and 3 < 9.
Step: 4
Substitute 4 in the expression, 3 × 4 = 12 and 12 > 9.
Step: 5
Substitute 3 in the expression, 3 × 3 = 9 and 9 = 9.
Step: 6
So, the number 3 makes the expression true.
Q2Choose the number that replaces the blank to make the expression true.
___ ÷ 5 = 6

A. 20
B. 35
C. 30
D. 11

Step: 1
Substitute the choices in the expression to check which number makes the expression true.
Step: 2
Substitute 20 in the expression, 20 ÷ 5 = 4 and 4 < 6.
Step: 3
Substitute 35 in the expression, 35 ÷ 5 = 7 and 7 > 6.
Step: 4
Substitute 30 in the expression, 30 ÷ 5 = 6 and 6 = 6.
Step: 5
So, the number 30 makes the expression true.
Q3Which of the numbers will make the expression true?
3 × ___ = 9

A. 3
B. 2
C. 4

Step: 1
Substitute the choices in the expression to check which number makes the expression true.
Step: 2
Substitute 2 in the expression, 3 × 2 = 6 < 9.
Step: 3
Substitute 3 in the expression, 3 × 3 = 9 = 9.
Step: 4
Substitute 4 in the expression, 3 × 4 = 12 > 9.
Step: 5
So, the number 3 makes the expression true.
Q4Which number would make the equation true?
8 × 2 = 27 - ___

A. 11
B. 9
C. 8
D. 13

Step: 1
We multiply 8 with 2 to get the left hand side of the expression.
Step: 2
So, the expression would be 16 = 27 - ___.
Step: 3
Substitute the choices in the above expression to check which number would make the expression true.
Step: 4
Substitute 8 in the expression, 27 - 8 = 19 and 19 > 16.
Step: 5
Substitute 9 in the expression, 27 - 9 = 18 and 18 > 16.
Step: 6
Substitute 13 in the expression, 27 - 13 = 14 and 14 < 16.
Step: 7
Substitute 11 in the expression, 27 - 11 = 16 and 16 = 16.
Step: 8
So, the number 11 makes the equation true.
Q5Find the unknown number in the number sentence.

_________ × 6 = 72

A. 12
B. 11
C. 13
D. 14

Step: 1
Substitute the choices in the expression to check which number makes the expression true.
Step: 2
Substitute 13 in the expression, 13 × 6 = 78 and 78 > 72.
Step: 3
Substitute 11 in the expression, 11 × 6 = 66 and 66 < 72.
Step: 4
Substitute 14 in the expression, 14 × 6 = 84 and 84 < 72.
Step: 5
Substitute 12 in the expression, 12 × 6 = 72 and 72 = 72.
Step: 6
So, the number 12 makes the expression true.
Q6Find the unknown number in the number sentence.

__________ × 6 = 96

A. 12
B. 16
C. 14
D. 13

Step: 1
Substitute the choices in the expression to check which number makes the expression true.
Step: 2
Substitute 13 in the expression,13 × 6 = 78 and 78 < 96.
Step: 3
Substitute 12 in the expression,12 × 6 = 72 and 72 < 96.
Step: 4
Substitute 14 in the expression,14 × 6 = 84 and 84 < 96.
Step: 5
Substitute 16 in the expression,16 × 6 = 96 and 96 = 96.
Step: 6
So, the number 16 makes the expression true.
Q7Find the unknown number in the number sentence.
18× ____ = 90

A. 7
B. 5
C. 6
D. 8

Step: 1
Substitute the choices in the expression to check which number makes the expression true.
Step: 2
Substitute 6 in the expression, 18× 6 = 108 and 108 > 90.
Step: 3
Substitute 7 in the expression, 18 × 7 = 126 and 126 > 90.
Step: 4
Substitute 8 in the expression, 18 ×8 = 144 and 144 > 90.
Step: 5
Substitute 5 in the expression, 18 × 5 = 90 and 90 = 90.
Step: 6
So, the number 5 makes the expression true.
Q8Find the unknown number in the number sentence.
36 ÷ ______ = 18

A. 4
B. 1
C. 2
D. 3

Step: 1
Substitute the choices in the expression to check which number makes the expression true.
Step: 2
Substitute 1 in the expression, 36 ÷ 1 = 36 and 36 > 18.
Step: 3
Substitute 3 in the expression, 36 ÷ 3 = 12 and 12 < 18.
Step: 4
Substitute 4 in the expression, 36 ÷ 4 = 9 and 9 < 18.
Step: 5
Substitute 2 in the expression, 36 ÷ 2 = 18 and 18 = 18.
Step: 6
So, the number 2 makes the expression true.
Q9Find the unknown number in the number sentence.
_________ ÷ 2 = 5

A. 22
B. 20
C. 4
D. 10

Step: 1
Substitute the choices in the expression to check which number makes the expression true.
Step: 2
Substitute 4 in the expression, 4 ÷ 2 = 2 and 2 < 5.
Step: 3
Substitute 20 in the expression, 20 ÷ 2 = 10 and 10 > 5.
Step: 4
Substitute 22 in the expression, 22 ÷ 2 = 11 and 11 > 5.
Step: 5
Substitute 10 in the expression, 10 ÷ 2 = 5 and 5 = 5.
Step: 6
So, the number 10 makes the expression true.
Q10Find the missing number.
× 9 = 81

A. 8
B. 5
C. 6
D. 9

Step: 1
Recall nine times-table.
1 × 9 = 9
2 × 9 = 18
3 × 9 = 27
4 × 9 = 36
5 × 9 = 45
6 × 9 = 54
7 × 9 = 63
8 × 9 = 72
9 × 9 = 81
Step: 2
So, 9 × 9 = 81
Step: 3
Therefore, the missing number is 9.
Q11Choose the number that replaces the blank to make the expression true.
4 ÷ ____ = 4

A. 4
B. 5
C. 2
D. 1

Step: 1
Substitute the choices in the expression to check which number makes the expression true.
Step: 2
Substitute 2 in the expression, 4 ÷ 2 = 2 and 2 < 4.
Step: 3
Substitute 4 in the expression, 4 ÷ 4= 1 and 1 < 4.
Step: 4
Substitute 1 in the expression, 4 ÷ 1= 4 and 4 = 4.
Step: 5
So, the number 1 makes the expression true.
Q12Which of the numbers will make the expression true?
____ × 2 = 8

A. 3
B. 2
C. 4
D. 8

Step: 1
Substitute the choices in the expression to check which number makes the expression true.
Step: 2
Substitute 3 in the expression, 3 × 2 = 6 and 6 < 8.
Step: 3
Substitute 2 in the expression, 2 × 2 = 4 and 4 < 8.
Step: 4
Substitute 8 in the expression, 8 × 2 = 16 and 16 > 8.
Step: 5
Substitute 4 in the expression, 4 × 2 = 8 and 8 = 8.
Step: 6
So, the number 4 makes the expression true.
Q13Find the missing value.
13 × ____ = 26

A. 3
B. 4
C. 1
D. 2

Step: 1
Substitute the choices in the expression to check which number makes the expression true.
Step: 2
Substitute 1 in the expression, 13 × 1 = 13 and 13 < 26.
Step: 3
Substitute 3 in the expression, 13 × 3 = 39 and 39 > 26.
Step: 4
Substitute 4 in the expression, 13 × 4 = 52 and 52 > 26.
Step: 5
Substitute 2 in the expression, 13 × 2 = 26 and 26 = 26.
Step: 6
So, the number 2 makes the expression true.